Financial distress, growth opportunities, and dividend policy on firm value through company hedging policies: Empirical study on property and real estate companies listed on indonesian stock exchange - Sudarma, I Putu; Sari, Maria M. Ratna (International research journal of management, IT and social sciences, 2020)
This study aims to obtain empirical evidence of the effect of financial distress, growth opportunities, and dividend policies on firm value through company hedging policies. This research was conducted on property and real estate companies listed on the Indonesian stock exchange in 2016-2018. The sampling technique used purposive sampling, with several criteria, to get a sample size of 55 companies. The data analysis technique used is path analysis. Hypothesis testing shows that financial distress has a positive effect on hedging, while growth opportunities and dividend policy have no significant effect on hedging. Financial distress hurts firm value. Growth opportunities and dividend policy have a positive effect on firm value. This study also found that hedging has no significant effect on firm value. Also, this study is unable to prove the company’s hedging policy as a mediating variable.